Environmental and Lifestyle Factors in the Onset of Pancreatic Cancer: A 10-Year Study from Kosovo as a Transitioning Country in Southeast Europe - Kreshnike Dedushi Hoti; Jeton Shatri; Flaka Pasha; Masum Rahman; Jona Kosova; Leotrim Berisha; Mirlinda Berisha; Arruj Hassan; Abu Bakar Siddik (International Journal of Biomedicine)
Background: Pancreatic cancer is one of the deadliest malignancies worldwide, with increasing incidence and mortality, particularly in low- and middle-income countries. This study investigates the role of environmental and lifestyle factors in the development of pancreatic cancer in Kosovo, a transitioning country in Southeast Europe. Methods and Results: A retrospective analysis was conducted on 519 patients diagnosed with pancreatic cancer at the University Clinical Center of Kosovo, from 2012 to 2022. Demographic, clinical, and environmental exposure data were collected, including air pollutant levels from national monitoring agencies. The study revealed a 200% increase in cases over ten years, with the highest burden among males (63%) and those aged 60–69. Urban centers, especially Prishtina, reported the highest incidence. Concurrently, levels of fine particulate matter (PM₂.₅), sulfur dioxide (SO₂), and nitrogen dioxide (NO₂) rose by 35%, 19%, and 22%, respectively. Modifiable risk factors, such as smoking (35.5%), type 2 diabetes (35.5%), and alcohol use (8.5%), were prevalent. Conclusions: There is a strong association between increased pancreatic cancer incidence and long-term exposure to air pollution in Kosovo. Environmental pollutants, compounded by modifiable lifestyle factors, may be critical in disease onset, warranting urgent public health interventions.